2020
DOI: 10.1111/jcmm.14983
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B6 inhibits macrophage activation to prevent lipopolysaccharide‐induced acute pneumonia in mice

Abstract: Macrophage activation participates in the pathogenesis of pulmonary inflammation. As a coenzyme, vitamin B6 (VitB6) is mainly involved in the metabolism of amino acids, nucleic acids, glycogen and lipids. We have previously reported that activation of AMP‐activated protein kinase (AMPK) produces anti‐inflammatory effects both in vitro and in vivo. Whether VitB6 via AMPK activation prevents pulmonary inflammation remains unknown. The model of acute pneumonia was induced by injecting mice with lipopolysaccharide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…Clinical trials found an inverse relationship between vitamin B6 intake and the risk of Parkinson's disease and Alzheimer's disease 34,35 . A new study showed that vitamin B6 supplementation effectively prevented lung inflammation 15 . In the present study, vitamin B6 prevented toxic shock by suppressing excessive inflammation, which was consistent with the previous research 14 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Clinical trials found an inverse relationship between vitamin B6 intake and the risk of Parkinson's disease and Alzheimer's disease 34,35 . A new study showed that vitamin B6 supplementation effectively prevented lung inflammation 15 . In the present study, vitamin B6 prevented toxic shock by suppressing excessive inflammation, which was consistent with the previous research 14 .…”
Section: Discussionsupporting
confidence: 91%
“…Vitamin B6 suppresses NF‐κB activation and NLRP3‐mediated caspase‐1 activation 13,14 . Another study showed that vitamin B6 activated AMPK phosphorylation to inhibit LPS‐induced macrophage activation by activating DOK3 15 . Consistent with these results, vitamin B6 was found to reduce the expression of pro‐inflammatory cytokines via suppression of NF‐κB and MAPK signalling pathways.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…While some preclinical, translational, early-stage, as well as late-stage clinical studies, have yielded promising positive data regarding the clinical impact potential of ascorbic acid, thiamine, riboflavin, niacinamide, and pyridoxine (Vit. B6) in the prevention and treatment of CRS, coagulopathy, ALI, acute kidney injury (AKI), ARDS, and MODS in the context of sepsis (Li, 2018;Hager et al, 2019;Putzu et al, 2019;Iglesias et al, 2020;Obi et al, 2020;Noormandi et al, 2020;Shan et al, 2020), other studies have not shown any meaningful activity (Fujii et al, 2020 Jan 17;Moskowitz et al, 2020). For example, Moskowitz et al recently reported the results of a 205-patient, randomized blinded, multicenter study of ascorbic acid, thiamine and steroids in patients with septic shock that was performed at 14 centers in the United States Patients were randomly assigned to receive parenteral ascorbic acid (1,500 mg), hydrocortisone (50 mg), and thiamine (100 mg) every 6 h for 4 days (n 103) or placebo in matching volumes at the same time points (n 102) (ClinicalTrials.gov Identifier: NCT03389555) (Moskowitz et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Rejuveinix (RJX) (Van Wyk et al) is a formulation of several vitamins, including ascorbic acid (Vitamin C), cyanocobalamin (Vitamin B12), thiamine hydrochloride (Vitamin B1), riboflavin 5′ phosphate (Vitamin B2), niacinamide (Vitamin B3), pyridoxine hydrochloride (Vitamin B6), calcium D-pantothenate, and magnesium sulfate, representing components that have been studied in animal models of septic shock and ARDS as well as clinical studies in septic patients (Lev et al, 2007;Wang et al, 2014;Li, 2018;Woolum et al, 2018;Hager et al, 2019;Iglesias et al, 2020;Pan et al, 2019;Putzu et al, 2019;Noormandi et al, 2020;Obi et al, 2020;Shan et al, 2020;Uckun et al, 2020). Here we are reporting for the first time the primary safety and pharmacokinetics (PK) data from a phase 1 clinical study of RJX and the results of a nonclinical pharmacodynamics study that evaluated its activity in a mouse model of sepsis, ARDS, and multi-organ failure.…”
Section: Introductionmentioning
confidence: 99%